The effect of aspartic acid and glycine on amorphous calcium carbonate (ACC) structure, stability and crystallization - Rodriguez-Blanco, Juan (Elsevier, 2014)
The effect of organic molecules on CaCO3 crystallization, in particular on the formation of the initial amorphous calcium carbonate (ACC) phase, is poorly understood despite this knowledge being crucial for designing biomimetic compounds with specific function, strength and stability. We monitored ACC crystallization in the presence of varying concentrations of aspartic acid (ASP) and glycine (GLY). We observed an increase in ACC lifetime with increasing amino acid concentrations and showed that the amino acid molecules sorbed onto the ACC particles. However, little if any difference in composition and atomic structure or the so formed ACC was observed. Similarly, the crystallization pathway of ACC via vaterite and calcite although delayed, was only slightly affected by the added amino acids. The only exemption was at the highest tested ASP concentration where ACC formation was inhibited, The calcite crystals that formed in the presence of ASP had rounded edges and rough surfaces, features that are not observed for the pure, inorganic calcite or calcite formed in the presence of GLY. Overall, the results suggest that the amino acids affected ACC lifetime through the inhibition of crystal nucleation and growth, more so in the presence of ASP than GLY.
PUBLISHED
Keywords: Amorphous calcium carbonate (ACC); ACC lifetime; CaCO3 crystallization; Amino acids; Bimineralization; Nanoscience & Materials